2006
DOI: 10.1007/s00415-006-0277-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of highly active antiretroviral therapy (HAART) on psychomotor performance in children with HIV disease

Abstract: There was no significant difference in psychomotor functioning between children newly treated, previously treated and untreated with HAART over the course of one year. Psychomotor performance deteriorated after 12 months of HAART, which provides important indications concerning the lack of benefits of HAART on psychomotor functions in children despite immunologic reconstitution. Further research with larger sample sizes is needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
(50 reference statements)
1
24
0
1
Order By: Relevance
“…Koekkoek and others have concluded that ART alone is not sufficient to reverse the neurodevelopmental consequences of pediatric HIV infection 20,44 and ART may even contribute to neuromotor decline 44 . In American children, studies found that only 1 of 13 neuropsychological measures significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Koekkoek and others have concluded that ART alone is not sufficient to reverse the neurodevelopmental consequences of pediatric HIV infection 20,44 and ART may even contribute to neuromotor decline 44 . In American children, studies found that only 1 of 13 neuropsychological measures significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Three computerized tasks of the Amsterdam Neuropsychological Tasks (ANT) system were used to quantify attention/alertness, motor coordination, and executive functions [2,3]. Alertness was evaluated by the mean of the reaction time (msec) to 32 visual stimuli and the inconsistency of alertness by the standard deviation of the 32 reaction times.…”
Section: Emethods 3 Tests and Questionnaires To Assess Neurocognitivmentioning
confidence: 99%
“…Children who have been critically ill at young age suffer from a substantial neurocognitive deficit when assessed years after admission to the pediatric intensive care unit (PICU) [1][2][3][4][5]. This neurocognitive legacy comprises, besides lower scores for intelligence, visual-motor integration, memory and behavior, also an important deficit in executive functions, motor coordination and attention [1].…”
Section: Introductionmentioning
confidence: 99%
“…The current treatment options for children with either progressive or static encephalopathy are primarily limited to ART, a combination of three or more antiretrovirals that have at least two mechanisms of action by which they disrupt viral replication [26]. Many antiretrovirals, such as zidovudine and stavudine, readily penetrate the BBB, enabling them to directly reduce the damage caused by HIV in the CNS by preventing the release of neurotoxic proteins through the inhibition of viral replication [27, 28].…”
Section: Antiretroviral Therapymentioning
confidence: 99%
“…Despite the use of ART, delays in motor and language abilities first observed in early childhood may persist as infected children age [9]. While several studies have demonstrated that therapeutic intervention with antiretroviral compounds for HIV-infected children have facilitated performance within the normal range on global intelligence tests [26, 2931], specific cognitive domains and neurobehavioral functions may remain impaired. School-age children with HIV encephalopathy frequently perform more poorly than uninfected children on tests of global intelligence and on more-detailed cognitive measurements; these children also perform poorly on tasks of fine motor skills and exhibit deficits in language and vocabulary skills [26].…”
Section: Limitations Of Artmentioning
confidence: 99%